Analysis of Public Relations Communication Strategies in Introducing Digital Banking to Customers - Eka Anindya, Nasywa; Wiradendi Wolor, Christian; Marsofiyati (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This research aims to analyze the public relations communication strategy in introducing digital banking services at Bank X. This research uses a qualitative approach by collecting data through interviews, observation, and document analysis. The results showed that the communication strategy implemented involved a combination of digital media campaigns and face-to-face approaches. Social media platforms such as Instagram and YouTube were used to reach younger audiences, while customer service provided direct assistance to customers who were less familiar with digital technology. The results showed that the strategy was effective in increasing customer awareness of digital banking features, athough challenges such as knowledge gaps and customer hesitancy in using technology still existed. To overcome these challenges, the bank adopted a personalized approach though in-person consultations and strengthened the educational content with interactive tutorials. This research highlights the importance of integrating digital and offline communication strategies to bridge the technology literacy gap and increase customer adoption of digital banking services.